MEMAHAMI KONSEP MAQASHID AL-SYARIAH DALAM FILSAFAT HUKUM ISLAM - Sitti Najmah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2017)
AbstractMaqashid al-syariah is target and meaning desired by syara in specifying or it all or most his lawses, or target oves and specified secret God in each God law. This, Maqashid al-syariah is existing secret and target and desired God in specifying, ad for as a whole and some of laws of God. Target of syariah, at the core of is to look after kindliness of human being and obviate badness, either in world and in eternity/the beyond.Theory of maqashid al syariah becoming fulcrums the core important is kindliness of human being in eternity/the beyond and world. This matter, new earn isnt it if five fundamental element can be realized and looked after. Ad for fundamental element, is to look after religion, soul, mind, clan and look after estae.Kata Kunci: Maqashid dan al-syariah